Comparative analysis between the theories of road transport safety and emission - Ádám Török (Transport, 2017)
In this paper, author’s aim is to investigate the tendencies of EU27 countries based on road transport safety and road transport-related CO2 emission. On EU level huge efforts have been made in order to reduce the number of fatal road accidents and to reduce the CO2 emission as well. There is a strong revealed driving force behind the connection of road fatalities and social mortalities. The main research question is if there is such a tendency behind the time-series of road transport-related CO2 reduction? Author has used the tools of mathematical statistics in order to investigate the phenomena and to reveal the interdependencies.